2022
DOI: 10.1364/boe.457467
|View full text |Cite
|
Sign up to set email alerts
|

Brain white matter morphological structure correlation with its optical properties estimated from optical coherence tomography (OCT) data

Abstract: A pilot post-mortem study identifies a strong correlation between the attenuation coefficient estimated from the OCT data and some morphological features of the sample, namely the number of nuclei in the field of view of the histological image and the fiber structural parameter introduced in the study to quantify the difference in the myelinated fibers arrangements. The morphological features were identified from the histopathological images of the sample taken from the same locations as the OCT images and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…CP OCT technology detects polarization-dependent changes and, therefore, represents a promising tool for the assessment of the state of connective tissue in breast cancer and its differentiation from areas of tumor cell clusters based on the registration of cross-polarization backscattering of the OCT signal [29,38]. In addition, in this study, a more recent method of measuring the attenuation coefficient, known as the depth-resolved approach [42,43,46], was used, while in other studies on the evaluation of attenuation coefficient in breast tissue linear fitting method was used [30]. The advantages of the depth-resolved approach involve avoiding axial resolution deterioration from the fitting range and inaccurate attenuation coefficient measurements due to a poor choice of fitting range.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…CP OCT technology detects polarization-dependent changes and, therefore, represents a promising tool for the assessment of the state of connective tissue in breast cancer and its differentiation from areas of tumor cell clusters based on the registration of cross-polarization backscattering of the OCT signal [29,38]. In addition, in this study, a more recent method of measuring the attenuation coefficient, known as the depth-resolved approach [42,43,46], was used, while in other studies on the evaluation of attenuation coefficient in breast tissue linear fitting method was used [30]. The advantages of the depth-resolved approach involve avoiding axial resolution deterioration from the fitting range and inaccurate attenuation coefficient measurements due to a poor choice of fitting range.…”
Section: Discussionmentioning
confidence: 98%
“…A number of studies have shown that CP OCT is a promising method for differentiating tumorous from non-tumorous breast tissue [29,38] and human brain tissue [39], as well as for the diagnosis of bladder cancer [40]. CP OCT can also measure the attenuation coefficient, which can be helpful for improving and increasing the contrast between tumorous and non-tumorous breast tissues [41][42][43]. Various morphological features of breast cancer are anticipated to influence the polarization qualities of tumor tissue differently.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that areas of damaged white matter are structurally heterogeneous because the tumor has a complex effect on the tissue of the pathways (4). On the one hand, there is a destruction of myelinated nerve fibers, the exact mechanism of which has not yet been established (30). In our previous work (31), we carried out a quantitative assessment of the relationship between the morphological and optical properties of normal white matter, and it was shown that myelinated fibers make the main contribution to its scattering properties.…”
Section: Att(co)mentioning
confidence: 99%
“…The CP OCT method is sensitive to changes of light polarization in tissues. Changes of polarization plane in biological tissues may be caused by double refraction or by microscopic scattering anisotropy [ 13 , 14 ]. This allows to detect anisotropic tissue structures which longitudinally exceed transverse dimensions significantly [ 15 ].…”
Section: Introductionmentioning
confidence: 99%